Case Report: Extended survival in KRAS-G12V NSCLC with leptomeningeal metastasis through integrated intrathecal chemotherapy and systemic therapies - Chen, Yun; Qin, Zhiquan; Zhan, Luying; Guo, Xinchang; Fukuda, Koji; Zhou, Qihao (Frontiers in Pharmacology, 2025)
Leptomeningeal metastasis (LM) is among the most severe complications in lung cancer patients, particularly for those without targetable gene mutations, who typically survive just 1–4 months. We present the case of a 68-year-old man with non-small cell lung cancer (NSCLC) and LM (pT1cN0M1b, stage IVB) whose primary lesion was early-stage with no other distant metastases. Genetic testing identified only a KRAS-G12V mutation. After neurological symptoms progressed following one cycle of pemetrexed, bevacizumab plus platinum-based chemotherapy, the patient underwent ventriculoperitoneal shunt placement and Ommaya reservoir implantation. Treatment with intrathecal pemetrexed via the Ommaya reservoir, combined with intravenous tislelizumab and carboplatin, resulted in 12 months of progression-free survival. For subsequent central nervous system progression involving both brain parenchymal metastasis and LM, we administered whole brain radiotherapy followed by second-line intrathecal thiotepa via Ommaya reservoir alongside tislelizumab and bevacizumab. This achieved continued shrinkage of brain lesions and neurological improvement. After ten cycles, thrombocytopenia necessitated switching to intrathecal methotrexate. Remarkably, the patient has survived nearly 29 months while maintaining good performance status and quality of life - to our knowledge, one of the longest reported survival for an NSCLC patient with LM harboring KRAS-G12V or other non-targetable mutations. This case suggests that combining ventriculoperitoneal shunt with Ommaya reservoir-delivered intrathecal chemotherapy may represent an effective therapeutic approach for LM patients.